2022
DOI: 10.47115/bsagriculture.983345
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Diseases in Fish

Abstract: Fungal diseases of fish have become increasingly important, over the past 20 years. The traditional ''fungi'' are comprised of members from several different taxonomic kingdoms. An increasing number of other environmental fungi are being reported from diseased fish, further testament to the opportunistic nature of many fungi. Active fungal agents living in waters cause infections in juvenile and adult individuals in fish populations, leading to decay in eggs and larvae. Fungal infections that are generally obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Among the diseases causing economic losses in global salmon aquaculture, parasites, such as amoebic gill disease (Neoparamoeba pemaquidensis, Paramoeba pemaquidensis, Acanthamoeba castellanii, A. astronyxis) [5][6][7] are significant; as are, fungal diseases including saprolegniosis (Saprolegnia parasitica, S. invaseris) [8][9][10], aphanomycosis (Epizootic ulcerative syndrome (EUS) Aphanomyces invadans) [11,12], ichthyosporidiosis (Ichthyophonus hoferi), and others [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Among the diseases causing economic losses in global salmon aquaculture, parasites, such as amoebic gill disease (Neoparamoeba pemaquidensis, Paramoeba pemaquidensis, Acanthamoeba castellanii, A. astronyxis) [5][6][7] are significant; as are, fungal diseases including saprolegniosis (Saprolegnia parasitica, S. invaseris) [8][9][10], aphanomycosis (Epizootic ulcerative syndrome (EUS) Aphanomyces invadans) [11,12], ichthyosporidiosis (Ichthyophonus hoferi), and others [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, other than physical injuries, previous reports have already demonstrated that excessive skin damage in teleost is mainly from pathogenic infection. And these unhealing wounds of skin may further advance to systemic fatal diseases, such as Aeromonas hydrophila (A. hydrophila) mediates septicemia while Pseudomonas uorescens induces saprolegniasis [5,6]. The above-mentioned evidence implies a decisive role of immune responses in participating in teleost wound healing.…”
Section: Introductionmentioning
confidence: 99%